Ethnobotany and Folk Pharmaceutical Properties of Major Trees or Shrubs in Northeast of Iran - Jalali, H.; Mozaffari Nejad, A.S.; Ebadi, A.G.; Laey, G. (Asian Journal of Chemistry, 2010)
An ethnopharmacognostic survey on the traditional pharmaceutical knowledge of old and newly introduced natural remedies used for healing humans in two small mountainous area in Semnan province of Iran. Approximately 56 medicine species of trees or shrubs belongs to 27 families were recorded. The objectives of this study were to introduce important useful parts and their medicinal characteristic them in two indigenous region. It is found that all these plants used by the rural people in traditional uses and food consumption that the mainly of them included: Juniperus communis, Berberis vulgaris, Alnus glutinosa, Carpinus betulus. Alnus subcordata, Cornus australis, Corylus avelana, Crataegus oxycantha, Rhamnus palassi, Ilex aquifolivm, Lonicera caprifolia, Mespilus germaniac, Tillia platyphllus, Paliuarus spina Christi, Prunus spinosa, Quercus castaneafolia, Rosa canina, Hypericum androsaemum, Rubus fruticosus. Salix alba, Smilax excels, Taxus baccata, Viscum album, Cerasus spp, Mespilus sp and Pyrus spinosa. The common use of the aerial parts of Hypericum and Rosamum and the leaves of Morus alba against cough, migraine and healing wounds. Fleshy female cone of Juniperus communis against urinary trace infection. Crataegus for heart tonic and Salix alba against rheumatic pain. The studies presented here could suggest new inputs for further photochemical and pharmacological studies among Iranian folk pharmacopoeia and also for sustaining environmentally integrated projects focuses on of the maintenance of traditional pharmaceutical knowledge via breading or controlled gathering activities of local medicinal species.